2013
DOI: 10.1038/srep02511
|View full text |Cite
|
Sign up to set email alerts
|

Subdiffusion Supports Joining Of Correct Ends During Repair Of DNA Double-Strand Breaks

Abstract: The mobility of damaged chromatin regions in the nucleus may affect the probability of mis-repair. In this work, live-cell observation and distance tracking of GFP-tagged DNA damage response protein MDC1 was used to study the random-walk behaviour of chromatin domains containing radiation-induced DNA double-strand breaks (DSB). Our measurements indicate a subdiffusion-type random walk process with similar time dependence for isolated and clustered DSBs that were induced by 20 MeV proton or 43 MeV carbon ion mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 37 publications
1
41
0
1
Order By: Relevance
“…Focused particle microbeams are a potentially effective way to probe the interaction of the DSB formed along different particle tracks. For example, Girst et al . used live‐cell observations and distance tracking of the GFP‐tagged DNA damage response protein MDC1 to study the random‐walk behavior of DSB formed in chromatin domains by 20 MeV proton and 43 MeV carbon ions.…”
Section: Model Testing and Clinical Validation Of Rbe Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Focused particle microbeams are a potentially effective way to probe the interaction of the DSB formed along different particle tracks. For example, Girst et al . used live‐cell observations and distance tracking of the GFP‐tagged DNA damage response protein MDC1 to study the random‐walk behavior of DSB formed in chromatin domains by 20 MeV proton and 43 MeV carbon ions.…”
Section: Model Testing and Clinical Validation Of Rbe Modelsmentioning
confidence: 99%
“…Focused particle microbeams [152][153][154][155][156][157][158][159] are a potentially effective way to probe the interaction of the DSB formed along different particle tracks. For example, Girst et al 160 used live-cell observations and distance tracking of the GFP-tagged DNA damage response protein MDC1 to study the random-walk behavior of DSB formed in chromatin domains by 20 MeV proton and 43 MeV carbon ions. They found that the subrandom-walk confinement of DSB to domains smaller than the diameter of the cell nucleus increases correct break-end rejoining and decreases the chance of long-range movements and, therefore, also decreases the chance pairwise DSB interactions create lethal chromosome aberrations.…”
Section: Model Testing and Clinical Validation Of Rbe Modelsmentioning
confidence: 99%
“…A DSB causes local changes in the mobility of chromatin; modeling predicts an increased mobility due to entropic effects [78], but motion in vivo is subdiffusional [79] which reduces the probability of long-range movements. The broken ends adopt more peripheral positions in chromosomes [78], favoring their meeting and rejoining.…”
Section: Finding Targets In the Genomementioning
confidence: 99%
“…It has been experimentally demonstrated that double strand breaks move by sub-diffusion (Girst et al, 2013;Lucas et al, 2014;Miné-Hattab et al, 2017), and, although not explicitly concluded, there is experimental evidence that this applies to individual double strand break ends (Soutoglou et al, 2007). To the best of our knowledge this type of motion has not yet been explicitly included in any mechanistic in silico models of DNA repair.…”
Section: Motionmentioning
confidence: 99%